ESG, Ownership Structure, and Board Composition Effects on Tax Avoidance in Indonesian Manufacturing - Febby Taniya; Agrianti Komalasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Sekolah Tinggi Ilmu Ekonomi Krakatau, 2026)
Purpose: This study aims to analyze the effect of ESG performance, institutional ownership, and the proportion of female directors on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange from 2022 to 2024. Methodology: This study uses a quantitative approach with a balanced panel dataset of 19 companies, yielding 57 observations selected through purposive sampling. Tax avoidance is proxied by the Effective Tax Rate (ETR), while firm size and profitability serve as control variables. The analysis was conducted using a Random Effect Model with Panel EGLS (Swamy-Arora) in EViews. Results: ESG performance and the proportion of female directors had no significant effect on tax avoidance. Institutional ownership has a significant negative effect on tax avoidance, indicating that higher institutional ownership reduces aggressive tax-avoidance practices. Conclusions: The findings suggest that institutional ownership effectively monitors management and curbs opportunistic behavior related to tax avoidance, while ESG disclosure and female director representation are currently insufficient to significantly influence tax strategies in the Indonesian manufacturing context. Limitations: This study is limited by a small sample (19 firms), reliance on a single ESG data source, and a short post-pandemic period. Future research should expand the sample, separate ESG dimensions, and explore alternative tax avoidance proxies, such as Cash ETR or Book-Tax Differences. Contribution: This study provides empirical evidence on the factors of corporate governance and sustainability that affect tax avoidance in Indonesia, offering insights for regulators, investors, and companies to improve monitoring mechanisms and corporate reporting practices.